Origanum syriacum L. Attenuates the Malignant Phenotype of MDA-MB231 Breast Cancer Cells - AlKahlout, Amal; Fardoun, Manal; Mesmar, Joelle; Abdallah, Rola; Badran, Adnan; Nasser, Suzanne A.; Baydoun, Serine; Kobeissy, Firas; Shaito, Abdullah; Iratni, Rabah; Muhammad, Khalid; Baydoun, Elias; et al. (Frontiers in Oncology, 2022)
Breast cancer is the leading cause of cancer-related deaths among women. Among breast cancer types, triple negative breast cancer (TNBC) is the most aggressive, and is resistant to hormonal and chemotherapeutic treatments. As such, alternative approaches that may provide some benefit in fighting this debilitating pathology are critically needed; hence the utilization of herbal medicine. Origanum syriacum L., one of the most regularly consumed plants in the Mediterranean region, exhibits antiproliferative effect on several cancer cell lines. However, whether this herb modulates the malignant phenotype of TNBC remains poorly investigated. Here, we show that in MDA-MB-231, a TNBC cell line, Origanum syriacum L. aqueous extract (OSE) inhibited cellular viability, induced autophagy determined by the accumulation of lipidized LC3 II, and triggered apoptosis. We also show that OSE significantly promoted homotypic cell-cell adhesion while it decreased cellular migration, adhesion to fibronectin, and invasion of MDA-MB-231 cells. This was supported by decreased activity of focal adhesion kinase (FAK), reduced α2 integrin expression, and downregulation of secreted PgE2, MMP2 and MMP-9, in OSE-treated cells. Finally, we also show that OSE significantly inhibited angiogenesis and downregulated the level of nitric oxide (NO) production. Our findings demonstrate the ability of OSE to attenuate the malignant phenotype of the MDA-MB-231 cells, thus presenting Origanum syriacum L. as a promising potential source for therapeutic compounds for TNBC.